ОБҐРУНТУВАННЯ НЕОБХІДНОСТІ РЕГУЛЮВАННЯ СОЦІАЛЬНО-ТРУДОВИХ ВІДНОСИН В УМОВАХ ВІЙНИ - Vuychenko, Maryna (Zhytomyr Ivan Franko State University, 2023)
The article analyzes the current state of social and labor relations and determines the need for their regulation in the conditions of the ongoing war on the territory of Ukraine. Factors affecting the implementation of effective social policy in the field of labor relations are substantiated. The article states that social and labor relations are relations between the worker, the employer and the state, aimed at meeting the social needs of each of the participants in these relations in the process of using labor and its results. They are the basis, social and economic foundation of any economic system, the "core" of the entire complex of social relations, since the quality of working life, social and labor relations in society, labor productivity and, ultimately, socio-economic progress. The article emphasizes that in the conditions of the war, which is currently ongoing, and the introduction of martial law by the President of Ukraine, it is important to return to the study of the problem of regulating social and labor relations and outline the main features of the use of labor resources during the war, to determine ways to increase labor efficiency and productivity, the real state of employment and unemployment, etc. The article notes that the norms of labor legislation, which were successfully operating in the pre-war period, are undergoing changes in accordance with the realities of today. Thus, in accordance with Article 43 of the Constitution of Ukraine, the state creates conditions for the full exercise of the right to work by citizens, guarantees equal opportunities in choosing a profession and type of activity, implements programs of vocational training, training and retraining of personnel in accordance with public needs. The article emphasizes that an important element of managing social and labor relations is the conclusion of labor contracts between employers and employees. The martial law regime prompts employers to enter into labor contracts, first of all, taking into account the following requirements: the need for the prompt involvement of new workers in the performance of work, the elimination of personnel shortages, including due to the actual absence of workers due to evacuation and migration to relatively safe regions of Ukraine, and abroad, as well as the loss of working capacity of a part of the combatants